Energy loss of relativistic projectiles in non-ideal electron liquids (International Journal of Mathematics and Physics, 2013)
The energy loss of relativistic projectiles in collisional one-component plasmas is analyzed within the method of moments. Both the canonical and non-canonical solutions of the Hamburger moment problem corresponding to five convergent power frequency moments of the electron plasma loss function are employed with the static, purely imaginary, Nevanlinna parameter with the imaginary part iqual to the collision frequency calculated within the Green-Kubo formalism in terms of static structure factors evaluated in the HNC approximation using the Deutsch effective potential.Thus we take into account the dissipation processes in the plasma. It is pointed out that the correlations only slightly influence the deviation of the stopping power with the relativistic corrections taken into account from the classical Bethe-Bohr-Larkin asymptotic form.